Unbundling the Moral Dispute About Unbundling in South Africa - Rossouw, Gedeon J. (Journal of business ethics, 1997)
Unbundling -- or the breaking up of conglomerates into smaller independent companies -- normally has very little to do with morality, because decisions to unbundle are usually taken on pure strategic business grounds. However, the way unbundling was introduced into the debate about the restructuring of the South African economy by the African National Congress (ANC), gave unbundling some very distinct moral undertones. In this paper the moral arguments in support of and in opposition to unbundling within the South African context are identified. It is then argued that these rival sets of arguments can be related back to two different sets of moral convictions about redistributive justice. The author argues that the impact of the prevailing moral dissensus on moral decision-making should be given due consideration when dealing with moral disputes such as unbundling. In the final part of the paper an illustration is given of how the moral dispute about unbundling should be approached amidst the mentioned moral dissensus.